Pelatihan Penyusunan Strategi Kampanye Politik Untuk Meningkatkan Elektabilitas Kader Partai Politik Perempuan di Provinsi Aceh - Nurdin Nurdin; Restu Rahmawati; Fatkhuri Fatkhuri (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The problem of the low level of women's political representation in the regional legislature has become a serious concern for the community and various interest groups in Aceh Province. Identification of this problem explains that this condition is caused by the low skills of female political cadres in designing appropriate and efficient political campaign strategies. The use of social media through the platforms Facebook, Twitter, Instagram and YouTube is an important aspect in designing a political communication strategy to increase the electability of women's political party cadres ahead of regional legislative elections. This training aims to increase the electability of female political party cadres by utilizing social media as a political campaign strategy to potential voters in the constituency. This training uses a conceptual approach, theory and practice. The results of this training show that the participants have gained knowledge and technical skills in designing political campaign strategies through social media which are expected to increase their electability to compete in the political contestation of the upcoming legislative elections.